Assessing the efficacy of borrower-based macroprudential policy using an integrated micro-macro model for European households - Marco Gross; Francisco Javier Población García (European Central Bank (ECB), 2016)
We develop an integrated micro-macro model framework that is based on household survey data for a subset of the EU countries that the Household Finance and Consumption Survey (HFCS) contains. The model can be used for conducting scenario and sensitivity analyses with regard to the factors that drive households' income and expenses as well as their asset values and hence the structure of their balance sheet. Moreover, we use it for the purpose of assessing the efficacy of borrower-based macroprudential instruments, namely loan-to-value (LTV) ratio and debt service to income (DSTI) ratio caps. The simulation results from the model can be attached to bank balance sheets and their risk parameters to derive the impact of the policy measures on their capital position. The model framework also allows quantifying the macroeconomic feedback effects that would result from the policy-induced reduction of demand for mortgage loans. The model allows answering the question as to which of the two measures – LTV or DSTI caps – are more effective, both with respect to their ability to reduce household loss rates as well as their impact on the economy.
Keywords: C33; E58; G18; 330; household balance sheets; macro-financial linkages; macroprudential policy; stress-testing